2002
DOI: 10.2166/wst.2002.0156
|View full text |Cite
|
Sign up to set email alerts
|

A new process for the combined treatment of municipal wastewaters and landfill leachates in coastal areas

Abstract: One of the most convenient methods for leachate control is to treat landfill leachates with domestic wastewaters. In this framework, a two-stage treatment system including anaerobic pre-treatment combined with a chemical post-treatment system such as ammonia stripping and/or Magnesium Ammonium Phosphate (MAP) precipitation can be comparable with a conventional secondary biological treatment. In this study, 2.5% and 2% of leachate by volume was mixed with domestic wastewater as the feed for the mesophilic Upflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Li et al [38,39] [76] and Altinbas et al [3] studied MAP precipitation after anaerobic pre-treatment of domestic wastewater and landfill leachate mixture. Maximum ammonia lowering was obtained as 66% at a pH of 9.3 at the stochiometric ratio whereas ammonia lowering reached to 86% at the same pH above the stochiometric ratio.…”
Section: Coagulation-flocculationmentioning
confidence: 99%
“…Li et al [38,39] [76] and Altinbas et al [3] studied MAP precipitation after anaerobic pre-treatment of domestic wastewater and landfill leachate mixture. Maximum ammonia lowering was obtained as 66% at a pH of 9.3 at the stochiometric ratio whereas ammonia lowering reached to 86% at the same pH above the stochiometric ratio.…”
Section: Coagulation-flocculationmentioning
confidence: 99%
“…Land application of sewage sludge is a viable method of nutrient (i.e., nitrogen and phosphorus) soil fertilization; this has increased during recent years due to economic and environmental reasons (Straub et al 1993;Westrell et al 2004;Gale 2005). It has however, been shown that spreading sludge on agricultural land both facilitates the circulation of pathogens in the environment and also leads to the contamination of potable waters via surface runoff (Chauret et al 1999;Yangin et al 2002;Hutchison et al 2005) posing a threat to human and animal health. Disposal of sewage sludge in municipal landfill can result in the contamination of waste liquor with human pathogens (Sobsey 1978;Yangin et al 2002;Szostakowska et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has however, been shown that spreading sludge on agricultural land both facilitates the circulation of pathogens in the environment and also leads to the contamination of potable waters via surface runoff (Chauret et al 1999;Yangin et al 2002;Hutchison et al 2005) posing a threat to human and animal health. Disposal of sewage sludge in municipal landfill can result in the contamination of waste liquor with human pathogens (Sobsey 1978;Yangin et al 2002;Szostakowska et al 2004). Such pathogens usually occur in raw sewage sludge and sewage sludge end products in high concentration due to the fact that they precipitate during wastewater processing (Straub et al 1993;Yangin et al 2002;Westrell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum COD and turbidity removals obtained were 25.7 and 36.4%, respectively. However, Yangin et al [37] and Ozturk et al [14] obtained about 50% COD removal with MAP precipitation of anaerobically treated leachate [24,37]. Kapdasli et al [38] stated that COD removal in MAP process is due to the adsorption of organics onto the surface of MAP crystals, so the differences in the COD removal efficiencies could be attributed to the different physical properties of crystals formed during MAP precipitation.…”
Section: Map Precipitationmentioning
confidence: 99%